Optimal fractional order interval type-2 fuzzy controller for upside-down asymmetric multilevel inverter based dynamic voltage restorer to accurately compensate faulty network voltage - Darvish Falehi, Ali; Torkaman, Hossein (Journal of ambient intelligence and humanized computing, 2023)
The power quality issue becomes an important concern for the electric power companies, sensitive loads and manufacturers due to deregulation in power supply systems. This paper aims to enhance the power quality features in the distribution system using novel structure of Dynamic Voltage Restorer (DVR). This costume power device can operate in its best compensation performance and functionality in case that both the control system and multilevel inverter components to be reconditioned. Toward this subject, this paper proposes three following novelties: (1) Upside–Down Asymmetrical Multi-Level Inverter (UDAMLI) topology with reduced structure to create high-step staircase sinusoidal voltage with consideration of low semiconductor switches. (2) Fractional Order Interval Type-2 Fuzzy System (FOIT2FS) for triggering angle control system to create accurate d-q modulation index. (3) Optimal design of triggering angle control system using Stochastic Fractal Search (SFS) to create required voltage reference signals. The aforementioned novelties have significantly upgraded the AC voltage synthesizer part so that DVR can accurately compensate all voltage disturbances such as voltage sag, voltage swell and voltage harmonic distortion. Three different voltage disturbances have been considered to test and analyze the compensation capability of the proposed DVR. Meanwhile, the FOIT2FS-based DVR has been compared with PID, PI α D β , IT1FS and IT2FS to validate its accuracy and robustness. In the main, the simulation results achieved by proposed compensator and other compensators reveal the high compensation performance of FOIT2FS-based UDAMLI-DVR with trivial Total Harmonic Distortion (THD). Furthermore, it can be stated that the major findings of this paper which are related to the DVR structure are: enhancing the accuracy and compensation capability, reducing the semiconductor count and increasing the cost-effectiveness.